Neuroprotective potential of new chromones isolated from the soil actinomycete Microbispora sp. TBRC6027 - Suchada Kittisrisopit; Nantiya Bunbamrung; Chitti Thawai; Sarin Tadtong; Nantawan Niemhom; Somjit Komwijit; Pranee Rachtawee; Pattama Pittayakhajonwut (My University, 2019)
Nine new chromone analogs (1–9) were isolated from the soil actinomycete Microbispora sp. TBRC6027. The chemical structures were determined based upon NMR spectroscopic methods. These compounds were evaluated in vitro by using P19-derived neurons for neuroprotective activity against oxidative stress induced by serum deprivation and showed % viability of neurons at the concentration of 1 ng/mL varied from 43.51% to 52.99% without significant neurotoxicity for P19-derived neurons at the same concentration. Moreover, all tested compounds were inactive for antibacterial activity against both Gram-positive and Gram-negative bacteria and for cytotoxicity against MCF-7 (human breast cancer) and Vero cells at maximum tested concentration 50 μg/mL. However, compounds 4, 6, and 7 displayed weak cytotoxicity against NCI-H187 (human small-cell lung cancer) cells with IC50 in a range of 87.99–91.57 μM.
Keywords: Neurotoxicity; Viability assay; Vero cell; Synthesis of Organic Compounds